Robot-assisted radical prostatectomy with da Vinci single-port system - Kurowski, Marek; Kuczapska, Karolina; Gliwa, Anna; Ryglewicz, Monika; Fabian, Dariusz; Leszczyńska-Knaga, Elżbieta; Jakubczyk, Natalia; Rutkowska-Kawalec, Weronika; Moczydłowski, Paweł; Michalczuk, Karolina (Journal of Education, Health and Sport, 2025)
Introduction and purpose Prostate cancer is the most common malignant tumor in men in Poland. In 2021, the standardized incidence rate was 48.2 cases per 100,000 people. It is diagnosed mainly in men over 60 years of age. The choice of treatment method depends on the stage of the disease, general condition and age of the patient. Treatment mainly includes surgery, radiotherapy and hormone therapy. In the case of surgical procedures, it is possible to perform prostate cancer surgery using the Da Vinci single-port surgical robot. The aim of this literature review is to describe the procedure of radical prostatectomy using the da Vinci single-port robot and to assess the effectiveness of radical prostatectomy using the da Vinci single-port robot compared to open and laparoscopic prostatectomy. Material and methods This review of studies was based on articles obtained from the scientific database PubMed. Key search terms included prostate cancer; robot-assisted radical prostatectomy; robotic surgery; da Vinci Surgical System; da Vinci single-port; laparoscopic prostatectomy; open prostatectomy. Conclusions Currently, the da Vinci single-port surgical system is playing an increasingly important role in radical prostatectomy centers. It is increasingly replacing open radical prostatectomies due to its higher treatment efficacy and fewer complications. However, no significant differences have been demonstrated compared to classical laparoscopic surgery. Further studies are also necessary to assess functional and oncological results.